100th anniversary of the discovery of ferroelectricity: How it impacted the current day physics. Issue 1 (9th December 2020) - Bhalla, Amar S.; Saxena, Avadh; Guo, Ruyan; Taylor, George W.
Abstract: The year 2020 marks hundred years since the watershed discovery of the phenomenon of ferroelectricity although at that time its importance was hardly realized. We provide a historical account of this event and its impact in terms of new materials discovery, novel fundamental physics concepts and technological applications on a decadal basis. We emphasize how ferroelectrics and the broader class of ferroics enriched our understanding of not only a wide variety of functional materials including multiferroics but also numerous device concepts and even a slew of topological defects these materials can harbor. Finally, we touch upon the current as well as future research topics in this ever growing and fecund area of interdisciplinary science.